FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN MAKAN PADA REMAJA - Chindy Annisa Putri Mandala Sempaga (Perhimpunan Kesehatan Holistik Indonesia, 2021)
The case numbers of eating disorders are now increasing with the times and can be affected anyone in various age groups, gender, ethnicity, or race. This condition, which is classified as a serious psychiatric disorder, can cause disability that is very detrimental to physical and psychosocial health and can even be life-threatening. The causes of eating disorders are complex and multifactorial. Therefore, this literature review study aims to reveal what factors can contribute to the incidence of eating disorders in adolescents which can then be considered in preventing and overcoming eating disorders problems in adolescents. The method used is a literature review of 26 NCBI journals. The results obtained that the factors associated with the incidence of eating disorders in adolescents include biological, psychological, environmental, and sociocultural factors.